Expansion, standardization, and densification of the criminal justice apparatus: recent developments in Brazil - Fonseca, David S. (Punishment & society, 2018)
The democratic transition in Brazil witnessed the return of civil liberties and the emergence of a legal framework based upon respect for human rights and the adoption of extensive social entitlements. In recent years, the reduction of poverty and upward social mobility have also transformed the country’s social structure. In spite of these welcome changes, however, crime and prison rates went through a steep upsurge during the same period, undermining many of these more positive social changes. A number of reasons underlie the emergence of this predicament, ranging from large structural shifts to the piecemeal adoption of harsher criminal laws. Enmeshed in these developments nonetheless there is also important institutional modifications in the configuration of the criminal justice system. The present argument seeks to understand how the recent thrust in the modernization of state institutions helped to create this situation of crisis. The expansion, densification, and standardization of the criminal justice apparatus has prompted its greater effectiveness and, thus, contributed to the current predicament of high crime rates and mass incarceration in the country.